A new method for titania thin film production: Thermionic vacuum arc method. (June 2017) - Şenay, Volkan; Özen, Soner; Pat, Suat; Geçici, Birol; Korkmaz, Şadan
In this research, transparent titania (TiO2 ) thin films were deposited on a glass microscope slide and on a flexible polyethylene terephthalate (PET) substrate under a high vacuum condition by means of the thermionic vacuum arc (TVA) method in a very short period of time (60 s). Optical properties and surface properties of the coated TiO2 surfaces are related to the structural changes of the coated layers due to ion energies and substrate effect. But obtained results are closely linked to literature values. Our analysis showed that the TVA method is an alternative method for low-temperature coatings and the produced films present important advantages for optical and industrial applications.